Assessing the impact of trawling on benthic megafauna: comparative study of video surveys vs. scientific trawling. (16th April 2021) - Jac, Cyrielle; Desroy, Nicolas; Duchêne, Jean-Claude; Foveau, Aurélie; Labrune, Céline; Lescure, Lyvia; Vaz, Sandrine
Abstract: Most studies about benthic community use small-scale sampling methods focused on the infauna such as grabs or box-corers. The benthic data collected by scientific trawl surveys in all European waters, in the frame of the Common Fishery Policy Data Collection Multiannual Program, can be used to study the impact of large-scale fisheries such as trawling. However, the catchability of trawls is very dependent on the nature of the seabed as well as resulting ground-gear adaptations. Due to its non-destructive nature and its ability to focus on benthic macro-epifauna, towed video sampling appears to be a good alternative to monitor the impact of trawling on benthic communities. In the present work, we studied the influence of fishery induced seabed abrasion and video characteristics on nine indices, which can be used to monitor the effect of trawling on benthic communities, was studied. Among them, three indices specific to fishery effect detection based on biological traits appeared to be the best performing benthic indices with video data: modified-Trawling Disturbance Index, partial-Trawling Disturbance Index, and modified sensitivity index. The effectiveness of these indices to monitor the effect of trawling was evaluated and compared between trawl and video sampling. This work has highlighted that video sampling could be a good alternative, or at least a complementary method, to scientific trawling to monitor the effect of trawling on benthic communities in European waters.